Freemasonry and Civil Society. Europe and the Americas (North and South), de Margaret C. Jacob y María Eugenia Vázquez Semadeni - Mejía, Rebeca (2026)
Review Freemasonry and Civil Society. Europe and the Americas (North and South) de Margaret C. Jacob y María Eugenia Vázquez Semadeni. Nueva York: Peter Lang, 2025. 155 páginas. ISBN-10: 1433198398. ISBN-13: 978-1433198397.